Annotated Primary Literature: A Professional Development Opportunity in Science Communication for Graduate Students and Postdocs - Melissa McCartney (American Society for Microbiology, 2018)
Formal training in communicating science to a general audience is not traditionally included in graduate and postdoctoral-level training programs. However, the ability to effectively communicate science is increasingly recognized as a responsibility of professional scientists. We describe a science communication professional development opportunity in which scientists at the graduate-level and above annotate primary scientific literature, effectively translating complex research into an accessible educational tool for undergraduate students. We examined different types of annotator training, each with its own populations and evaluation methods, and surveyed participants about why they participated, the confidence they have in their self-reported science communication skills, and how they plan to leverage this experience to advance their science careers. Additionally, to confirm that annotators were successful in their goal of making the original research article easier to read, we performed a readability analysis on written annotations and compared that with the original text of the published paper. We found that both types of annotator training led to a gain in participants’ self-reported confidence in their science communication skills. Also, the annotations were significantly more readable than the original paper, indicating that the training was effective. The results of this work highlight the potential of annotator training to serve as a value-added component of scientific training at and above the graduate level.